IMPLEMENTATION OF INFORMATION SYSTEMS IN MODERN OFFICE MANAGEMENT - Kurniasari, Putri; Afina; Harahap, Nasrun (International Journal of Multidisciplinary Reseach, 2025)
In the era of digital and globalization, Management Information Systems (MIS) are the key to modern office work efficiency. MIS supports data integration, rapid decision making, and process automation. However, challenges such as infrastructure, human resources, and work culture still hamper its implementation. This study offers a holistic approach to optimize MIS effectively and sustainably. This study uses a literature review method by analyzing various documents such as books, journals, letters, and digital data. Data is collected from official sources and expert discussions, then analyzed using a content analysis approach. This process includes interpretation, explanation, and drawing conclusions based on written documentation, voice, and images. Management Information Systems (MIS) are important in modern offices to improve efficiency, data integration, and technology-based decision making. With the support of cloud, IoT, and big data, MIS accelerates work processes. However, challenges such as human resources, infrastructure, and work culture require adaptive strategies for MIS implementation to be successful and sustainable. Implementation of Management Information Systems (MIS) is very important in modern offices to improve efficiency, accuracy, and real-time decision making. However, technical, human resources, and infrastructure challenges must be overcome with adaptive strategies. With proper planning and integration, MIS can create a productive and competitive work environment, and drive an organization's digital transformation.